Automated layout design of multi-span reinforced concrete beams using charged system search algorithm. Issue 3 (8th May 2018) - Uz, Mehmet Eren; Sharafi, Pezhman; Askarian, Mahya; Fu, Weiqing; Zhang, Chunmei
Abstract : Purpose: The preliminary layout design of structures impacts upon the entire design process and, consequently, the total cost. The purpose of this paper is to select the most economical layouts that satisfy structural and architectural requirements, while considering the reciprocal effects of cost factors and layout variables at the preliminary stages of design. Design/methodology/approach: This paper presents an automated method for cost optimization of geometric layout design of multi-span reinforced concrete (RC) beams subjected to dynamic loading by using the charged system search (CSS) algorithm. First, a novel cost optimization approach for geometric layout problems is introduced, in which both cost parameters and dynamic responses are considered in the preliminary layout design of beams. The proposed structural optimization problem with constraints on the static and dynamic equilibrium, architectural dimensions and structural action effects is solved using the CSS algorithm. Findings: The proposed CSS algorithm for solving the cost optimization problem can be easily used for optimizing the span lengths and is also capable of working with various cost functions. The presented examples show that the proposed algorithm using the new cost optimization function provides satisfactory results and can result in over 7 per cent cost saving. Originality/value: This is an original paper proposing a novel methodology for preliminary layout design of concrete beams.